2016
DOI: 10.1021/acs.jpcc.6b04557
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Studies of the Methanol Decomposition Reaction on Graphene-Supported Pt13 Nanoclusters

Abstract: Defective graphene has been shown experimentally to be an excellent support for transition-metal electrocatalysts in direct methanol fuel cells. Prior computational modeling has revealed that the improved catalytic activity of graphene-supported metal clusters is in part due to increased resistance to catalyst sintering and to CO poisoning, but the increased reaction rate for the methanol decomposition reaction (MDR) is not yet fully explained. Using density functional theory, we investigate the adsorption and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…334 Alloying Pt with other TMs (Fe, Co, Ni, Cu and Pd) also reinforce this downshift. 336 Gasper et al 337 have found that the support-induced shifts in catalyst electronic structure correlates well with an overall change in adsorption behavior of methanol decomposition reaction intermediates, and that the reaction thermodynamics are modified in a way that suggests the potential of greater catalytic activity for Pt13 on graphene ML with SV. Interestingly, in the same work, it was shown that adsorption energy predictors [338][339][340] established for traditional heterogeneous catalysis studies of methanol decomposition reaction on macroscopic crystalline facets are equally valid on supported nanocatalysts with irregular surface morphologies, see Figure 13.…”
Section: Platinummentioning
confidence: 99%
See 1 more Smart Citation
“…334 Alloying Pt with other TMs (Fe, Co, Ni, Cu and Pd) also reinforce this downshift. 336 Gasper et al 337 have found that the support-induced shifts in catalyst electronic structure correlates well with an overall change in adsorption behavior of methanol decomposition reaction intermediates, and that the reaction thermodynamics are modified in a way that suggests the potential of greater catalytic activity for Pt13 on graphene ML with SV. Interestingly, in the same work, it was shown that adsorption energy predictors [338][339][340] established for traditional heterogeneous catalysis studies of methanol decomposition reaction on macroscopic crystalline facets are equally valid on supported nanocatalysts with irregular surface morphologies, see Figure 13.…”
Section: Platinummentioning
confidence: 99%
“…Interestingly, in the same work, it was shown that adsorption energy predictors [338][339][340] established for traditional heterogeneous catalysis studies of methanol decomposition reaction on macroscopic crystalline facets are equally valid on supported nanocatalysts with irregular surface morphologies, see Figure 13. 337 Copyright 2016 from the American Chemical Society.…”
Section: Platinummentioning
confidence: 99%
“…40,41 In particular, graphene with carbon defects can provide anchor sites for supporting clusters and increase the stabilization of cluster bonding at the interface. 42,43 It is important to understand the interaction between the cluster and support so as to unravel the reaction mechanism and ultimately improve the catalytic performance.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] Particularly interesting are Pt clusters supported by graphitic materials, such as carbon black, carbon nanotubes, and graphene, which have been extensively studied both experimentally, [14][15][16][17][18][19][20] and theoretically. [21][22][23][24][25][26][27][28][29][30][31][32][33][34] A better catalytic activity of small Pt clusters supported by graphene sheets has been demonstrated experimentally. 16,17 These results lead to the hypothesis that downsizing the Pt clusters to single atoms can enhance the catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…36 The vacancies usually formed during the preparation are expected to have strong interactions with the Pt atoms as demonstrated in several theoretical studies. 23,31,32 Back et al have predicted the great potential of a single atom catalyst supported on defective graphene for CO 2 electroreduction applications. 37 However, the dispersion of the single Pt atoms on graphene is limited to the number of point defects.…”
Section: Introductionmentioning
confidence: 99%